2019
DOI: 10.3390/ma12050747
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of ZrC Barrier Coating on SiC-Coated Carbon/Carbon Composite Developed by Thermal Spray Process

Abstract: A thick ZrC layer was successfully coated on top of a SiC buffer layer on carbon/carbon (C/C) composites by vacuum plasma spray (VPS) technology to improve the ablation resistance of the C/C composites. An optimal ZrC coating condition was determined by controlling the discharge current. The ZrC layers were more than 70 µm thick and were rapidly coated under all spraying conditions. The ablation resistance and the oxidation resistance of the coated layer were evaluated in supersonic flames at a temperature exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 25 publications
(25 reference statements)
1
7
0
Order By: Relevance
“…These cracks act as the channels for oxygen penetration, which result in the oxidation of the SiC inner layer and formation of SiO 2 phase under the surface layer (Figure 15(e,f)). Thus, according to Figure 15, the observation of ZrC and SiC phases under the surface layer confirm the demonstrative effect of ZrO 2 layer as a protective and barrier layer against further oxidation during the ablation test [23,28,30].…”
Section: Ablation Test Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…These cracks act as the channels for oxygen penetration, which result in the oxidation of the SiC inner layer and formation of SiO 2 phase under the surface layer (Figure 15(e,f)). Thus, according to Figure 15, the observation of ZrC and SiC phases under the surface layer confirm the demonstrative effect of ZrO 2 layer as a protective and barrier layer against further oxidation during the ablation test [23,28,30].…”
Section: Ablation Test Resultssupporting
confidence: 72%
“…It has been reported that the voids or pores in the coating form due to the unmelted particles, confined vapours, and irregular deposition of splats on each other in the spray process [28,29]. The observed micro-cracks and inter splat cracks (in Figure 8) originate from the rapid solidification of coating from very high-temperatures to room temperature [23,28,30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Properties such as low neutron absorption, high strength, low thermal expansion coefficient, high thermal conductivity etc. make it a preferred choice for nuclear applications 3 5 . Graphite has been tested at all operating conditions of HTRs and has been found to fulfill the operational demands at high temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Another paper explores novel surface designs to develop thermally sprayed icephobic coatings [ 4 ]. With the emergence of new engineering materials such as composites, there is also an interest in implementing thermal spray approaches for imparting them suitable protection, as exemplified by the contribution focusing on ZrC barrier coatings deposited on SiC-coated carbon/carbon composites by vacuum plasma spraying [ 5 ]. Post-treatment of thermal sprayed coatings by adopting approaches such as shot peening and laser remelting has also been a subject of considerable academic research.…”
mentioning
confidence: 99%